A Numerical Simulation of Radiation Chemistry for Controlling the Oxidising Environment in Water-Cooled Nuclear Power Reactors - Dorota Swiatla-Wojcik (Applied Sciences, 2022)
Maintaining the integrity of materials of light-water nuclear power reactors requires the development of effective methods to control and minimise the corrosive environment associated with the radiolysis of a coolant. In this study, the behaviour of the oxidising environment is simulated using a hybrid method. The hybrid method has advantages in that the production of radiolytic species under exposure of the coolant to ionising radiation is simulated while providing material and charge balances. Steady-state concentrations of stable and transient oxidising agents are calculated as a function of radiation composition and dose rate by numerical integration of the system of kinetic equations describing radiation chemistry of neutral water, the alkaline solution, and the hydrogenated systems at 300 °C. The importance of the reactions and equilibria constituting the radiolysis scheme of the coolant is assessed. The influence of the presence of a base and the injected H2 on the yield of key reactions responsible for the formation of the main oxidants H2O2 and O2 are discussed. Simulation indicated the synergic effect of H2 gas and base added to the coolant on diminishment of the steady-state concentration of oxidants.